Accuracy analysis of various earthquake catalogs based on ground truth locations：Several M5 earthquakes in the southwest region of China - Jie Yang; Wangwang Gu; Han Zhang; Sidao Ni; Risheng Chu; Minhan Sheng; Baolong Zhang (地震科学进展)
Accurate epicenter location is crucial for assessing seismic hazards and risks, investigating seismicity, and exploring the Earth’s internal structure. Numerous global institutions routinely release earthquake catalogs, providing the earthquake source parameters such as epicenter locations. Nonetheless, disparities in epicenter locations reported by these catalogs can arise due to the variation in seismic station data, crust-mantle velocity models, and earthquake localization methodologies employed. InSAR data, characterized by its high spatial resolution, provides reasonable positional constraints on shallow earthquakes, offering ground truth (GT) and serving as a key basis for evaluating the accuracy of earthquake epicenter locations. This study selected a series of earthquakes of approximately magnitude 5 in Southwestern China, recorded by seismological and InSAR data. The discrepancies between the epicenter determinations of earthquake catalogs and InSAR measurements were compared to assess the accuracy of the China Earthquake Network Center (CENC) and USGS/NEIC catalogs in this specific region. The results indicate that the most significant discrepancy between the CENC catalog and InSAR-derived epicenters was 12 km, with longitudinal differences ranging from −0.04° to 0.13° and a marginally smaller latitudinal variance of −0.05° to 0.06°. In comparison, the maximum difference between the USGS earthquake catalog and InSAR epicenters was 20 km, with a longitudinal and latitudinal difference of −0.21°～0.13° and −0.10°～0.08°, respectively. The CENC catalog provided more accurate epicenter locations for most of the earthquake events. However, for individual events, the epicenter locations given by CENC deviate from the InSAR results by a significant amount, which may be attributed to the distribution of seismic stations, among other factors.